Cost-effective composite electrode for the fast voltammetric screening and determination of riboflavin (B2) and pyridoxine (B6) in pharmaceuticals - Dos Santos, Thiago A.D.; Barreto, Lucas N.; Ritta, Almir Guilherme S. L.; De Meneses, Wanessa S.; Nunes, Ronaldo S. [UNESP]; Semaan, Felipe S. (My University, 2013)
Different solid composites made by mechanical dispersions of graphite particles into heated paraffin (from 65 to 80% graphite, in mass) were prepared and assessed in order to optimize their use in electrochemical and electroanalytical procedures for bioanalysis. Besides these, composites were also evaluated by thermoanalytical techniques aiming to study their conservation and long-term stability (over eight months without special care), among others. Best results were found at 80% m/m graphite in paraffin. Such electrode combines low-cost, stability, sensitivity, ease of maintenance and clearance, besides the possibilities of manufacture in many different forms and shapes (with or without modifications) and applicability in a wide range of pH. Electrochemical studies by different voltammetric techniques involving vitamins from complex B (riboflavin and pyridoxine) leaded to a better understanding about their electrooxidative processes onto carbon-composite electrodes, specially regarding reversibility and pH-dependence. Data were also acquired and optimized with analytical purposes, being square-wave voltammetry in pH 4.2 chosen by its many advantages. Good linearity between peak responses as function of concentration were reached from 5 to 43 μmol L-1 for riboflavin (peak at -0.257 V) and up to 8.5 × 10-4 mol L -1 for pyridoxine (peak at +1.04 V), best studied conditions; limits of detection (at an S/N of 3) for both analites showed to be circa 1.0 mol L-1. Different commercial samples were analyzed for riboflavin (EMS® complex B syrup) and pyridoxine (Citoneurin 5000 Merck® ampoules) providing 96.6% and 98.7% recoveries, respectively.
Keywords: Composite electrodes; Pyridoxine; Riboflavin; Voltammetric analysis